1984
DOI: 10.1017/s0022172400060940
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological and bacteriological investigation ofSerratia marcescensepidemic in a nursery and in a neonatal intensive care unit

Abstract: SUMMARYAn epidemic caused by Serratia marcescens that involved 26 infants admitted to the Neonatal Intensive Care Unit (NICU) and 82 infants admitted to the Nursery of the 2nd Medical School of Naples is reported. Two different biotypes of S. marcescens with two completely different epidemiological patterns were identified. The prevalent biotype (A8b trigonelline-) was isolated in the delivery room, in the operating room, in the Nursery and in the NICU from items, healthy infant exereters and affected infants;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0
2

Year Published

1988
1988
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 28 publications
(24 reference statements)
1
10
0
2
Order By: Relevance
“…Outbreaks of Serratia marcescens are well documented, particularly outbreaks in neonatal units (14,16,27,31). One reported outbreak was caused by netilmicin-resistant S. marcescens shortly after netilmicin had been introduced as the primary aminoglycoside (16).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Outbreaks of Serratia marcescens are well documented, particularly outbreaks in neonatal units (14,16,27,31). One reported outbreak was caused by netilmicin-resistant S. marcescens shortly after netilmicin had been introduced as the primary aminoglycoside (16).…”
Section: Discussionmentioning
confidence: 99%
“…One reported outbreak was caused by netilmicin-resistant S. marcescens shortly after netilmicin had been introduced as the primary aminoglycoside (16). Outbreaks of amikacinresistant but tobramycin-susceptible Acinetobacter spp.…”
Section: Discussionmentioning
confidence: 99%
“…Outbreaks have been noted in neonatal and pediatric ICUs (4, 14, 18, 21, 28, 41, 60, 63, 74, 76, 88, 94, 95, 116, 133, 137, 150 , 198, 204, 215, 228, 239, 249, 250, 269, 270, 275, 309, 313, 338, 366, 393, 396, 400, 423), neonatal nurseries/units and special care baby units (7,100,156,190,238,275,310,359,362,387,423), pediatric oncology units (258), and maternity wards/hospitals (35,48).…”
Section: S Marcescensmentioning
confidence: 99%
“…From these pediatric nosocomial infection studies, many environmental sources or point sources have been found as reservoirs for S. marcescens, including hands of health care workers and exposure to health care workers (14,156,198,249,267,362,393,396,423), contaminated breast milk, formula, and breast pumps (133,156,204,274,393), contaminated parenteral nutrition (18), an infected neonate as the index patient or colonization of hospitalized infants (28,63,100,148,238,269,270,275,338,362,400), equipment such as incubators (28,198), laryngoscopes (95,204), suction tubes, soap dispensers (52), and waste jars (393), air conditioning ducts (387), contaminated hand brushes (7), contaminated disinfectants and soap (14,52,76,258,313,396), cotton wool pads (137), multidose nebulizer dropper bottles (215), and multidose medications (133).…”
Section: S Marcescensmentioning
confidence: 99%
“…Our first experience with the use of colistin for this purpose started in 1982. At that time we used MA supplemented with 200 i.u./ml colistin; in that previous study we investigated the circulation of S. marcescens strains during an outbreak in a neonatal intensive care unit (Montanaro et al 1984). The choice of this antibiotic as a selective agent depended upon the fact that resistance to colistin is very frequent in the genus Serratia and almost constant in S. marcescens (Grimont & Grimont, 1984).…”
Section: Discussionmentioning
confidence: 99%